The future of global value chains: business as usual or “a new normal”? - De Backer, Koen; Flaig, Dorothee (Paris, 2017)
"The rapid growth of global value chains (GVCs) has been an important driver of globalisation during the past decades. But the international fragmentation of production appears to have lost momentum and GVCs seem to have stalled in recent years. The world economy is facing a number of structural shifts that may dramatically change the outlook of GVCs in the coming years. The empirical evidence evaluating the potential impact of these shifts however largely lags behind, which makes these discussions somewhat speculative. By describing how these shifts will likely evolve over the next 10 to 15 years and calculating their effects on global production and trade, the scenarios in this paper offers new - empirically funded - insights on the future of GVCs."